ANALISIS PENGARUH BAURAN PEMASARAN DALAM USAHA MENINGKATKAN PENERIMAAN MAHASISWA BARU - Sundari & Antin Okfitasari (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
This study aims to examine the effect of marketing mix on increasing the number ofstudents at the Sekolah Tinggi Manajemen Informatika dan Komputer (STMIK) DutaBangsa Surakarta. Data collected by using sampling method as many as 117 studentrespondents. Data analysis was done through analysis of research instrument thatincluded validity test using product moment correlation and reliability test using alphaCronbach technique, hypothesis test included path analysis, coefficient of determination(R2), t test, F test and correlation analysis. The results of this study prove that 1).Maketing mix partially that has a significant influence on Increasing the Number ofStudents, is the variable Place, Promotion and People. 2). Marketing Mix simultaneouslythat has a significant influence on Increasing the Number of Students. 3). Placevariables have the most dominant influence on increasing the number of STMIK DutaBangsa Surakarta students compared with other variables.Keywords: independent and dependent variable, marketing mix, number of students